Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/insects10010001
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Effects of Petroselinum crispum (Umbellifereae) Essential Oil on the Pyrethroid Resistant Strains of Aedes aegypti (Diptera: Culicidae)

Abstract: In ongoing screening research for edible plants, Petroselinum crispum essential oil was considered as a potential bioinsecticide with proven antimosquito activity against both the pyrethroid susceptible and resistant strains of Aedes aegypti. Due to the comparative mosquitocidal efficacy on these mosquitoes, this plant essential oil is promoted as an attractive candidate for further study in monitoring resistance of mosquito vectors. Therefore, the aim of this study was to evaluate the impact of P. crispum ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…larvae. Enzymes such as phosphatases (alkaline and acidic), esterases, cytochrome 450, glutathione S-transferase, amylases, and acetylcholinesterase in insects perform functions of detoxification of xenobiotics and nutrition and are present mainly in larvae [ 45 , 46 , 47 ]. Alterations in the metabolism of these enzymes in insects can result in the capacity for resistance to insecticides when increased but death when inhibited or reduced, since they are responsible for detoxification and digestion, and hence are fundamental to the physiology of insects [ 13 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…larvae. Enzymes such as phosphatases (alkaline and acidic), esterases, cytochrome 450, glutathione S-transferase, amylases, and acetylcholinesterase in insects perform functions of detoxification of xenobiotics and nutrition and are present mainly in larvae [ 45 , 46 , 47 ]. Alterations in the metabolism of these enzymes in insects can result in the capacity for resistance to insecticides when increased but death when inhibited or reduced, since they are responsible for detoxification and digestion, and hence are fundamental to the physiology of insects [ 13 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Alkaline and acid phosphatases can act as defensive enzymes in the body by detoxification of insecticides and ingested fatty structures. However, changes in metabolism caused by botanical biocides can interrupt physiological processes, causing death [ 46 , 53 ]. Studies with extracts of Sapindus emarginatus against Ae .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies have shown the development of insect populations resistant to these insecticides. The temephos, for example, is an organophosphate that has contributed to the development of resistance in the mosquito 13,14 …”
Section: Introductionmentioning
confidence: 99%